Grid Integration of DC Buildings: Standards, Requirements and Power Converter Topologies - Edivan Laercio Carvalho; Andrei Blinov; Andrii Chub; Pietro Emiliani; Giovanni de Carne; Dmitri Vinnikov (IEEE Open Journal of Power Electronics, 2022)
Residential dc microgrids and nanogrids are the emerging technology that is aimed to promote the transition to energy-efficient buildings and provide simple, highly flexible integration of renewables, storages, and loads. At the same time, the mass acceptance of dc buildings is slowed down by the relative immaturity of the dc technology, lack of standardization and general awareness about its potential. Additional efforts from multiple directions are necessary to promote this technology and increase its market attractiveness. In the near-term, it is highly likely that the dc buildings will be connected to the conventional ac distribution grid by a front-end ac-dc converter that provides all the necessary protection and desired functionality. At the same time, the corresponding requirements for this converter have not been yet consolidated. To address this, present paper focuses on various aspects of the integration of dc buildings and includes analysis of related standards, directives, operational and compatibility requirements as well as classification of voltage levels. In addition, power converter configurations and modulation methods are analyzed and compared. A classification of topologies that can provide the required functionality for the application is proposed. Finally, future trends and remaining challenges pointed out to motivate new contributions to this topic.